Functional validation of putative toxin-antitoxin genes from the Gram-positive pathogen Streptococcus pneumoniae: phd-doc is the fourth bona-fide operon - Chan, Wai Ting; Yeo, Chew Chieng; Sadowy, Ewa; Espinosa, Manuel (Frontiers in Microbiology, 2014)
Bacterial toxin-antitoxin (TAs) loci usually consist of two genes organized as an operon, where their products are bound together and inert under normal conditions. However, under stressful circumstances the antitoxin, which is more labile, will be degraded more rapidly, thereby unleashing its cognate toxin to act on the cell. This, in turn, causes cell stasis or cell death, depending on the type of TAs and/or time of toxin exposure. Previously based on in silico analyses, we proposed that Streptococcus pneumoniae, a pathogenic Gram-positive bacterium, may harbor between four to ten putative TA loci depending on the strains. Here we have chosen the pneumococcal strain Hungary19A-6 which contains all possible ten TA loci. In addition to the three well-characterized operons, namely relBE2, yefM-yoeB, and pezAT, we show here the functionality of a fourth operon that encodes the pneumococcal equivalent of the phd-doc TA. Transcriptional fusions with gene encoding Green Fluorescent Protein showed that the promoter was slightly repressed by the Phd antitoxin, and exhibited almost background values when both Phd-Doc were expressed together. These findings demonstrate that phd-doc shows the negative self-regulatory features typical for an authentic TA. Further, we also show that the previously proposed TAs XreA-Ant and Bro-XreB, although they exhibit a genetic organization resembling those of typical TAs, did not appear to confer a functional behavior corresponding to bona fide TAs. In addition, we have also discovered new interesting bioinformatics results for the known pneumococcal TAs RelBE2 and PezAT. A global analysis of the four identified toxins-antitoxins in the pneumococcal genomes (PezAT, RelBE2, YefM-YoeB, and Phd-Doc) showed that RelBE2 and Phd-Doc are the most conserved ones. Further, there was good correlation among TA types, clonal complexes and sequence types in the 48 pneumococcal strains analyzed.